The Effect of Return on Assets and Capital Adequacy Ratio on Changes in Stock Prices (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2026)
The purpose of this study is to examine how changes in Bank Mandiri's stock price are impacted by the Return on Assets (ROA) and Capital Adequacy Ratio (CAR). One important metric that shows a company's worth to investors is its stock price, which also shows the company's financial success and future prospects. Since ROA is a metric of profitability that shows how well management can manage assets to produce profits, it was selected as the independent variable. Stock prices often rise in proportion to the ROA number, which indicates the company's capacity to provide returns for investors. On the other hand, CAR is a measure of bank capital health that characterizes how much capital the bank has on hand to cover the risk of loss. Investors typically view a high CAR level favourably since it shows that the bank can continue operational sustainability and financial stability, both of which have an impact on stock prices. Using secondary data from yearly banking financial reports and stock price data for the years 2010–2023, this study employs a quantitative methodology. The partial and simultaneous effects of ROA and CAR on changes in stock prices are investigated using multiple linear regression analysis. The findings indicate that ROA has no bearing on fluctuations in stock prices. Similarly, CAR has little impact on fluctuations in stock prices. In conclusion, Mandiri Banking Company's share price fluctuations from 2010 to 2023 are not influenced by factors such as profitability or capital sufficiency.
Keywords: Return on Asssets (ROA); Capital Adequacy; Ratio (CAR); Stock Price; Indonesia Stock Exhage